Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2019)
The second 2019 issue of SSLLT brings together six papers, all of which report empirical studies dealing with different aspects of teaching and learning additional languages in various contexts, and it also includes two book reviews. In the first contribution, Alastair Henry combines Hermans’ (2008) concept of the dialogical self with the tenets of complex dynamic systems theories (Hiver & Al-Hoorie, 2016) to investigate the developing professional identity of a preservice teacher of English during the practicum in a school in western Sweden. Using a combination of intra-personal data in the form of semi-structured interviews conducted before and after the practicum as well as inter-personal data in the form of forum postings and a stimulated recall discussion of a lesson taught by the participant, Henry shows that the construction of teacher identity entails interaction between present experiences and the imagined self. In the subsequent paper, Anne Huhtala, Anta Kursiša and Marjo Vesalainen seek to identify the motives driving 51 Finnish university students to learn foreign languages other than English, in this case French, German and Swedish, adopting as a theoretical framework Dörnyei’s (2009) theory of the L2 motivational self-system. Qualitative analysis of the narrative reflections written by the participants revealed that although the initial decisions to engage in language learning may be driven by social pressure, or the ought-to self, in the course of time it is the ideal self and the L2 learning experience that start to play the dominant role.